Success and failure in mathematics among standard seven students in the Bafokeng Region of Bophuthatswana. - Kiely, Joseph H (My University, 1990)
This researcn investigates success and failure in mathematics at the standard seven level in middle schools in the Bafokeng region. There is great concern expressed by parents, teachers and students about the high failure rate in this subject in the external examinations. Mathematics is seen to be important for securing good jobs in the platinum mines which are situated on the Bafokeng tribal lands. in general, greater efforts by teachers and students have made little impact on the public examination results. The present study undertakes ar xn-de th analysis of this problem in the anthropolog^/cal paradigm using the illuminatxve approach. Interviews and questionnaires are used for gathering data and triangulation techniques are used for verification and checking. Statistical correlation is applied to the variables but the study is not limited to numerical relationships between factors associated with scholastic success and failure. Two separate criteria of "success" are defined, namely the standard 7 mathematics mark and the performance of a ten per cent sample in each of five picture problems. The population xs composed of one educational unit: the one high school in Phokeng, capital of the Bafokeng, and the three middle schools which make up the catchment area of this high school. The number of students involved is approximately three thousand. Language and attitudes show strong positive correlations with both criteria of success. Other variables, like socio-economic status and degree of westernization are significantly related to the picture problem scores but not to the mathematics mark. Surprisingly, self-concept and embedded figures scores show no statistically significant relationship with either of the two criteria of success. In order to succeed in school mathematics a student must attain a high level of abstraction. This research does not suggest that the case is any different for Bafokeng students, buJj it attempts to explore the modes of perception, methods of concept formation and the development of appropriate schemata by which abstraction is achieved. Finally the Implications for teaching and learning of mathematics in school are discussed in the light of the findings of this research. This is the first study of its type, as far as can be ascertained, for Bophuthatswana schools.
A Thesis submitted to the Faculty of Education, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: Blacks -- Education -- South Africa -- Bophuthatswana; Mathematics -- Study and teaching (Secondary) -- South Africa -- Bophuthatswana.